A patterns of care analysis of hyperthermia in combination with radio(chemo)therapy or chemotherapy in European clinical centers - Ademaj, Adela; Veltsista, Paraskevi D.; Marder, Dietmar; Haelg, Roger A.; Puric, Emsad; Brunner, Thomas B.; Crezee, Hans; Gabrys, Dorota; Franckena, Martine; Gani, Cihan; Horsman, Michael R.; Krempien, Robert; et al. (Strahlentherapie und Onkologie, 2022)
Purpose The combination of hyperthermia (HT) with radio(chemo)therapy or chemotherapy (CT) is an established treatment strategy for specific indications. Its application in routine clinical practice in Europe depends on regulatory and local conditions. We conducted a survey among European clinical centers to determine current practice of HT. Methods A questionnaire with 22 questions was sent to 24 European HT centers. The questions were divided into two main categories. The first category assessed how many patients are treated with HT in combination with radio(chemo)therapy or CT for specific indications per year. The second category addressed which hyperthermia parameters are recorded. Analysis was performed using descriptive methods. Results The response rate was 71% (17/24) and 16 centers were included in this evaluation. Annually, these 16 centers treat approximately 637 patients using HT in combination with radio(chemo)therapy or CT. On average, 34% (range: 3-100%) of patients are treated in clinical study protocols. Temperature readings and the time interval between HT and radio(chemo)therapy or CT are recorded in 13 (81%) and 9 (56%) centers, respectively. The thermal dose quality parameter "cumulative equivalent minutes at 43 degrees C" (CEM43 degrees C) is only evaluated in five (31%) centers for each HT session. With regard to treatment sequence, 8 (50%) centers administer HT before radio(chemo)therapy and the other 8 in the reverse order. Conclusion There is a significant heterogeneity among European HT centers as to the indications treated and the recording of thermometric parameters. More evidence from clinical studies is necessary to achieve standardization of HT practice.
CRIS-Team WoS Importer:2022-09-09